The impact of globalization and its repercussions on Islamic banking activity and industry - Saad Abdul Qahar Sheikh (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
In the context of its new development, globalization has created an unprecedented economic and cultural environment, represented in commerce and electronic banking. The data of globalization has a significant impact on the activity and banking services in the third world towards the integration of banking and the transition to electronic banks comprehensive in order to diversify the sources of finance and employment in order to raise competitiveness and enhance the potential to address the banking risks. Islamic banks aim to represent the financial field of Islamic thought to collect funds and employ them to serve the society under the provisions of Islamic Sharia ... and rely on the means of investment and financing of their own derived from the Islamic shariah, such as Murabaha, speculation, peace, participation and others. The response of Islamic banks to globalization in the banking field has been weak. Most of them have not benefited from the development opportunities offered by globalization to the banking system, both in deepening the coordination and banking integration among them, with the aim of setting up giant international Islamic banking entities to raise their competitiveness or keep pace with the evolving developments of the banking industry And the activation and expansion of the work under the digital money and electronic systems of contemporary ... and the omission of the establishment of predictive strategic research centers for the Islamic banks to avoid the effects of financial crises and shocks that may face Banking system. Islamic banks have also failed to meet the requirements of Basel II standards, which have prevented the possibility of attracting international funding sources. It is noteworthy that limited efforts are being made to establish an international Islamic financial market in light of the rapid and effective transformation of the local financial markets towards international financial markets ... which resulted in the Islamic financial institutions being limited to Islamic banks and a number of investment and insurance companies.